Effect of Dietary Supplementation of Red Ginseng By-product on Laying Performance, Blood Biochemistry, Serum Immunoglobulin and Microbial Population in Laying Hens - H. K. Kang; S.-B. Park; C. H. Kim (Asian-Australasian Journal of Animal Sciences, 2016)
This study was carried out to investigate the effect of dietary supplementation of red ginseng by-product (RGB) on the laying performance, blood biochemistry, and microbial population in laying hens. A total of 120 Hy-Line Brown laying hens (75 weeks old) were randomly allotted to 1 of 3 dietary treatments with 4 replicates per treatment. A commercial-type basal diet was prepared, and 2 additional diets were prepared by supplementing 5.0 or 10.0 g/kg of RGB to the basal diet at the expense of corn. The diets were fed to hens on an ad libitum basis for 4 weeks. There were no differences in feed intake, egg weight, and feed conversion ratio during 4 weeks of the feeding trial. However, hen-day egg production was significantly greater (p<0.05) for the RGB treatment groups than that for the basal treatment group. There were no differences in triglyceride, aspartate aminotransferase, and alanine aminotransferase during the 4-week feeding trial. However, RGB supplementation increased (p<0.05) the serum immunoglobulin G (IgG) and IgM content compared with basal treatment group. The total cholesterol was lower (p<0.05) in the RGB treatments groups than that in the basal treatment group. The intestinal Lactobacillus population was greater (p<0.05) for the RGB treatments groups than that for the basal treatment group. However, the numbers of Salmonella and Escherichia coli were not different among dietary treatments. During the entire experiment, there was no significant difference in egg quality among all the treatments. In conclusion, in addition to improving hen-day production, there were positive effects of dietary RGB supplementation on serum immunoglobulin and cholesterol levels in laying hens.